PEMBERDAYAAN LITERASI KEUANGAN DAN PENTINGNYA MENABUNG BAGI SISWA DI SDN 02 PAMPANGAN - Yuliastanty, Susy; Nazif, Hazlif; Zumiarti, Zumiarti; Surya, Rahmad; Sunreni, Sunreni; Begawati, Nova; Al Fasyah Juliyus, Faridj; Saputra, Yudi; Nanda, Nanda (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
The level of financial literacy in Indonesia is still relatively low, especially among young children, so educational efforts are needed to instill a basic understanding of wise financial management. This community service activity aims to improve the financial literacy of elementary school students through education on the importance of saving. The activity was carried out at SDN 02 Pampangan with the involvement of 78 students in grades 4, 5, and 6. The implementation method used an educational and participatory approach, in the form of interactive material delivery, a